(3CfhGQ GdOQQ aj EjVGM GdMLQs - (3Ydj Hf eMeO Hf CjOeQ GdpLrdnOcj, YR GdOjf,J (B742 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdebOS Yf GdJQcjH hGdJMdjd hGdJTHjg hHYO aEf GdOGYj Zdi hVY YPY GdGTGQGJ GdeMQcI Gdj GjVGM eGSJQOg PhG GdYHGQGJ gh Gf Ggd ReGffG eef GJTZd HYde GdUfGYI s
(3BNQgG (B:s
(3aEPG MUQJ CfLH GdKeQ hGadM cPdc MGd gDdGA aj GdeOf GdGLJeGYjI hgPg GdGSQGQ GdJj GhO YfGcgG gj SQ Gddg dNGFajI s
(3GdfSNI HgG MhGTs
(3hHBNQg aGFOI aj GdUfGYIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B5 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B28s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdcjejGA h GdWHjYjGJs